2012
DOI: 10.1002/pip.2201
|View full text |Cite
|
Sign up to set email alerts
|

Development and experimental evaluation of a complete solar thermophotovoltaic system

Abstract: We present a practical implementation of a solar thermophotovoltaic (TPV) system. The system presented in this paper comprises a sunlight concentrator system, a cylindrical cup-shaped absorber/emitter (made of tungsten coated with HÍO2), and an hexagonal-shaped water-cooled TPV generator comprising 24 germanium TPV cells, which is surrounding the cylindrical absorber/emitter. This paper focuses on the development of shingled TPV cell arrays, the characterization of the sunlight concentrator system, the estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 38 publications
0
39
0
Order By: Relevance
“…Contrast to the conventional photovoltaic schemes with challenging-tailored solar irradiance, thermal spectrum in TPV can be flexibly tailored by using selective emitter [6e10] or fully utilized by advanced thermal management [11,12], providing some flexible strategies to achieve high power conversion efficiency. For instance, by developing high-performance selective emitter, Lenert et al [12] has recently realized TPV system efficiency up to 3.2%, whereas for the emitter relying on the intrinsic material properties, the reported system efficiency is no more than 1% [13], making the spectral management a hot topic among the TPV community.…”
Section: Introductionmentioning
confidence: 99%
“…Contrast to the conventional photovoltaic schemes with challenging-tailored solar irradiance, thermal spectrum in TPV can be flexibly tailored by using selective emitter [6e10] or fully utilized by advanced thermal management [11,12], providing some flexible strategies to achieve high power conversion efficiency. For instance, by developing high-performance selective emitter, Lenert et al [12] has recently realized TPV system efficiency up to 3.2%, whereas for the emitter relying on the intrinsic material properties, the reported system efficiency is no more than 1% [13], making the spectral management a hot topic among the TPV community.…”
Section: Introductionmentioning
confidence: 99%
“…By doing so, solar thermophotovoltaics promise to achieve high efficiency, by harnessing the entire solar spectrum; scalability and compactness, because of their solid-state nature; and dispatchablility, owing to the ability to store energy using thermal or chemical means. However, efficient collection of sunlight in the absorber and spectral control in the emitter are particularly challenging at high operating temperatures which has limited previous experimental demonstrations of this approach to conversion efficiencies around or below 1% [2]. STPV systems with structured surfaces with tailored spectral properties were theoretically predicted to achieve efficiencies exceeding 40%, however no such experimental demonstration has been reported in the literature.…”
Section: Solar Thermophotovoltaic Energy Conversionmentioning
confidence: 99%
“…For instance, ti λ is zero for the topmost subcell. Noticeably, although it is also beneficial for the rigorous detailed balance analysis to include the effect of photon recycling [2,28,29], e.g., luminescent recombination of the top subcell illuminating the bottom subcell, we have neglected this effect due to its secondary role and the difficulties in accurately quantifying its impaction on the realistic devices as a result of the systematic shortage of reliable optoelectronic properties for Sbbased alloys.…”
Section: Model and Calculationmentioning
confidence: 99%
“…In the latest experiment, benefiting from the employment of a nanophotonic thermophotovoltaic (TPV) emitter, Lenert et al [1] demonstrated an overall solar-to-electricity efficiency 3.2% in a realistic solar TPV system equipped with 0.55 eV GaInAsSb converters, showing threefold strong enhancement in comparison to previous works [2]. However, even for this improved result, little competitiveness could be demonstrated for TPV [3], since the result is still far below the one for commercially available photovoltaic technologies [4].…”
Section: Introductionmentioning
confidence: 98%